Socioeconomic factors and adolescent pregnancy outcomes: distinctions between neonatal and post-neonatal deaths? - Flick Louise H; Cook Rebeka; Markovitz Barry P; Leet Terry L (BMC, 2005)
Abstract Background Young maternal age has long been associated with higher infant mortality rates, but the role of socioeconomic factors in this association has been controversial. We sought to investigate the relationships between infant mortality (distinguishing neonatal from post-neonatal deaths), socioeconomic status and maternal age in a large, retrospective cohort study. Methods We conducted a population-based cohort study using linked birth-death certificate data for Missouri residents during 1997-1999. Infant mortality rates for all singleton births to adolescent women (12-17 years, n = 10,131; 18-19 years, n = 18,954) were compared to those for older women (20-35 years, n = 28,899). Logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI) for all potential associations. Results The risk of infant (OR 1.95, CI 1.54-2.48), neonatal (1.69, 1.24-2.31) and post-neonatal mortality (2.47, 1.70-3.59) were significantly higher for younger adolescent (12-17 years) than older (20-34 years) mothers. After adjusting for race, marital status, age-appropriate education level, parity, smoking status, prenatal care utilization, and poverty status (indicated by participation in WIC, food stamps or Medicaid), the risk of post-neonatal mortality (1.73, 1.14-2.64) but not neonatal mortality (1.43, 0.98-2.08) remained significant for younger adolescent mothers. There were no differences in neonatal or post-neonatal mortality risks for older adolescent (18-19 years) mothers. Conclusion Socioeconomic factors may largely explain the increased neonatal mortality risk among younger adolescent mothers but not the increase in post-neonatal mortality risk.